Painful piezogenic pedal papules - successful low level laser therapy - Mijailović, B.B. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Painful piezogenic pedal papules may be very difficult to treat. We describe two patients with this condition successfully treated with a low-level laser. A two-week treatment protocol induced a relatively longlasting pain relief without any side effects.
Keywords: Laser surgery; Skin diseases, papulosquamous; Therapy